Industrial engineering applications in emerging countries - Bidanda, Bopaya; Sabuncuoglu, Ihsan (Engineer); Kara, Bahar Y. (Bahar Yetis) (Boca Raton : CRC Press, 2015)
"Logistics management is one of the primal topics of Industrial Engineering. This book is the second volume of a three-volume series on global logistic management and focuses on recent developments and implementations of operations research techniques on some selected logistic problems in emerging countries. The book is composed of 10 chapters on topics ranging from quality management in pharmaceutical supply chains to risk analysis of maritime ports"--
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Industrial engineering -- Developing countries; Electronic books